VEGETATION, PHYTOMASS AND CARBON STORAGE IN NORTHERN EURASIA DURING THE LAST GLACIAL-INTERGLACIAL CYCLE AND THE HOLOCENE - Velichko A.A.; Zelikson E.M.; Borisova O.K. (My University, 1999)
The phytomass (the biomass of terrestrial vegetation) is one of the main reservoirs of carbon, as carbon makes up approximately 0.45 of the phytomass by weight [Ajtay, G.L., Ketner, P., Duvigneaud, P., 1979. Terrestrial primary production and phytomass. In: Bolin, B., Degens, E.T., Kempe, S., Ketner, P. (Eds.), The Global Carbon Cycle, SCOPE 13, Wiley, Chichester, pp. 123–181.]. During the glacial–interglacial climatic rhythm both composition and geographical distribution of vegetation over Northern Eurasia have been repeatedly subjected to major changes, accompanied by corresponding changes of phytomass and carbon storage. Of special interest are three key intervals within the last 125,000 years: the Mikulino (Eem) Interglacial optimum, about 125 ka BP; the Last Glacial maximum, 18–20 ka BP and the Holocene optimum, 5.5–6 ka BP. These intervals correspond to the extreme states of the environment. Vegetation which existed in Northern Eurasia 125, 18–20 and 5.5–6 ka BP, accumulated 377.1 Gt, 66.1 Gt and 292.1 Gt of phytomass, which corresponds to 169.7 Gt, 29.9 Gt and 131.4 Gt of carbon, respectively. Compared to present-day carbon storage in the phytomass of potential vegetation (taken as 100%), these values are 155%, 27% and 120%, respectively.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен